Framework for evaluating water quality information system performance - Hotto, Harvey P., author (Colorado State University. Libraries, 1994)
Water resource and water quality managers are being held increasingly accountable for the programs they manage. Much progress has been made in applying total systems perspectives to the design and operation of water quality monitoring and information programs, and towards rationalizing those programs with respect to management objectives and information needs. A recent example of that progress is the development of data analysis protocols to enhance the information system design process. However, further work is necessary to develop approaches which can help managers confront the water quality management environment of the future, which will be characterized by: (1) fewer purely technical questions, (2) more complex problems with social, economic, political and legal ramifications, and (3) actively managed and continuously improved water quality information systems. This research concludes that the management of water quality information systems for continuous improvement requires: (1) a competent system design process, (2) comprehensive documentation of system design and operation, and (3) a routine and thorough performance measurement and evaluation process. The framework for evaluating water quality information system performance presented in this dissertation integrates the experience of several disciplines into an instrument to help water quality managers accomplish these requirements. The framework embodies four phases: (1) evaluation planning, (2) watershed and management system analyses, (3) information system analysis, and (4) information system performance evaluation. The application of the framework is demonstrated in the evaluation of water quality monitoring programs associated with a unique municipal water transfer project. Water quality professionals of the U.S. Environmental Protection Agency and the U.S. Geological Survey are surveyed as to its potential application to large (e.g., regional or national) systems. Those exercises indicate the framework to be a convenient, economic, and flexible instrument useful towards enhancing water quality information system performance. Recommendations for future research to refine the framework and to extend its scope and utility are also presented.
Keywords: Water quality management; Information storage and retrieval systems -- Water quality